THE ROLE OF THE YOUNGER GENERATION IN PREVENTING THE SPREAD OF RELIGIOUS RADICALISM - Giani Adzkia; Hasuenah Wohseng (Universitas Pendidikan Indonesia, 2021)
The spread of radicalism never stops in the span of the history of Muslims from the past until now. Although radicalismis often associatedwith Islam, thereis no fact that Islam is a religion that teaches peace, there has never been an element of religious coercion against others and does not condone the practice of using violence in spreading religious understanding. Meanwhile, radicalism is an understanding that seeks to impose religious opinions, desires, and ideals to realize certain goals through the path of violence. The spread of radicalism can be a real threat to all circles, including the younger generation. The younger generation is more likely to be involved in radical groups, in addition the younger generation is often the main target in the spread of radical understanding because so far the younger generation is very easy to influence. But actually the younger generation has a very important role in preventing the spread of radicalism, considering the younger generation is the next generation of the nation that will challenge the future of the nation. Therefore, the role of the younger generation becomes very important in maintaining unity, unity and preventing the spread of radicalism.